The analysis of corruption - Patora, Krystyna (Studia Iuridica Toruniensia, 2019)
The present article discusses the source of the word „corruption”, legal regulations in the world and in Poland, including the Law of XII Tables, Ancient Rome, the Old Testament or in the Enlightement, and in the Polish law, starting from the Statute of Wiślica through the legal solutions passed in the Penal Code of 1932, other contemporary legal acts, the Penal Code of 1969 and present regulations concerning bribery. The matter of changing the regulations concerning corruption before joining the EU by Poland was raised, as well as the present legal status, including the regulation of corruption in sport and economy. The question of new areas of threat has been presented, including political corruption.